Quality and reflecting of financial position: an enterprises model through logistic regression and natural logarithm - Lulaj, Enkeleda (Journal of Economic Development, Environment and People, 2021)
The present study entitled "Quality and reflecting of financial position: an enterprises model through logistic regression and natural logarithm", determines the confirmatory effects of PRF analysis, to assess the position or condition of enterprises in the market. The business environment for enterprises shows the diversity of economic activity, but in one form or another they are interconnected, and their main purpose more specifically of the finance and accounting department, is to compile statements and financial reports (PRF) with reliable data where through them the enterprise looks at its financial position and orientation for better decision-making. The data of this research was based on primary and secondary data, such as interviews conducted in 100 enterprises and analysis of published PRFs. To achieve the purpose of the research from the interview and data, three categories of PRFs were used for testing the study hypothesis. Results from data processing in SPSS & R program, through tests and techniques within logistic regression and natural logarithm clearly show that there is an important relationship between the dependent variable and the independent ones and that large enterprises have a better financial position than small enterprises and the bankruptcy of small enterprises is greater